Cache Preemption Related Delay Accounting via Static Analysis and Functional Simulation - Starke, Renan Augusto; Oliveira, Rômulo Silva de Silva de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Cache memory related preemption delay causes large variations of the task execution time and tools that perform WCET static code analysis usually do not consider this behavior. The additional cache delays are usually solved by cache partitioning between tasks or they are incorporated in the schedulability analysis equations. This paper estimates the cache preemption delay of a task in two steps: task static analysis for the instruction cache and functional simulation for the data cache. Both steps are used to track the memory references. After that, we estimate which cache blocks may actually cause additional cache faults in a preemption. Due to the use of functional simulation, the calculated cache preemption delay is not the worst case, but this technique does not rely on WCET tools nor the real hardware. After this analysis, we determine the cost of preemption at each point of the program more accurately.